Estudos de alguns aspectos da alimentação em Ascia monuste Godart (Lepidoptera, Pieridae) - Felipe, Maria Cecília [UNESP]; Zucoloto, Fernando Sérgio [UNESP] (Sociedade Brasileira de Zoologia, 1993)
Six kinds of crucifer (broccoli, cabbage, califlower, kale, mustard and rugula) were tested, as food, for larvae od Ascia monuste. The best results were obtained eith califlower, broccoli, rugula and kale. Four sugars (glucose, fructose, sucrose and maltose) were tested to know their influence on the number of oviposition in female of Ascia monuste. The best results were obtained with fructose, glucose and sucrose.
Estudies on some aspects of the alimentation of Ascia monuste Godart (Lepidoptera, Pieridae)
Keywords: Lepidoptera; Pieridae; Ascia monuste; alimentation